2017
DOI: 10.1111/jam.13381
|View full text |Cite
|
Sign up to set email alerts
|

A loop-mediated isothermal amplification method for rapid direct detection and differentiation of nonpathogenic and verocytotoxigenicEscherichia coliin beef and bovine faeces

Abstract: The multiplex LAMP assay represents a rapid alternative to culture for monitoring E. coli levels on beef for hygiene monitoring purposes, and, potentially, a method for detection of VTEC in beef and faeces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Furthermore, actual samples from poultry farms were tested directly with the LAMP assays, and in all types of the samples tested, APEC-associated virulence genes were detected. The applicability of this LAMP method to direct detection of E. coli has been reported previously for beef and bovine feces samples (Stratakos et al, 2017), minced meat (Ravan et al, 2016), milk (Yang et al, 2014), lettuce (Xue-han et al, 2013), stool samples (Song et al, 2005; Teh et al, 2014), and others. In the present study, we have shown that this LAMP method is also applicable for direct testing of various environmental samples (e.g., feed, feces, air sampled in PBS buffer) as well as of tissues of the internal organs of chickens.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, actual samples from poultry farms were tested directly with the LAMP assays, and in all types of the samples tested, APEC-associated virulence genes were detected. The applicability of this LAMP method to direct detection of E. coli has been reported previously for beef and bovine feces samples (Stratakos et al, 2017), minced meat (Ravan et al, 2016), milk (Yang et al, 2014), lettuce (Xue-han et al, 2013), stool samples (Song et al, 2005; Teh et al, 2014), and others. In the present study, we have shown that this LAMP method is also applicable for direct testing of various environmental samples (e.g., feed, feces, air sampled in PBS buffer) as well as of tissues of the internal organs of chickens.…”
Section: Discussionsupporting
confidence: 55%
“…Although some qPCR cyclers are portable, the DNA extraction process that is needed prior to the qPCR amplification is the limiting step for on-site application. Also, the LAMP method is not sensitive to inhibitory effects from different sample matrices, and so it can be used for direct testing of samples without the need for their purification (Kogovšek et al, 2017; Stratakos et al, 2017) and can be applied on site for fast diagnosis (Tang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the assay specificity, no cross-reactions were reported when 58 bacterial strains and specimens was used. Limit of detection for this assay was reported to be 10 3 -10 2 CFU per g, which may be adequate to be used for monitoring hygienic status of beef and to control food-borne diseases caused by VTEC (Stratakos et al 2017).…”
Section: Multiplex Lampmentioning
confidence: 99%
“…A novel mLAMP was developed by Stratakos et al (2017) for detection and differentiation of nonpathogenic Escherichia coli and verocytotoxigenic E. coli (VTEC) in beef and bovine faeces. The mLAMP assay was designed for the detection of generic E. coli (nonpathogenic) targeting the phoA gene and VTEC strains targeting the stx1 or stx2 genes at 65°C for 30 min.…”
Section: Multiplex Lampmentioning
confidence: 99%